Molecular methods to investigate adhesion, transmigration, invasion and intracellular survival of the foodborne pathogen campylobacter jejuni - Backert, Steffen; Hofreuter, Dirk (Journal of Microbiological Methods, 2013)
Campylobacter jejuni is a spiral-shaped Gram-negative pathogen and major agent of gastrointestinal foodborne illness in humans worldwide. This pathogen encodes numerous described pathogenicity-associated factors involved in important processes including bacterial adhesion to, transmigration across, invasion into and intracellular survival within intestinal epithelial cells. This review article highlights various molecular techniques applied in the studies of each of these individual steps of C. jejuni host cell interactions in vitro including gentamicin protection assay, chemotaxis and motility assays, transwell and intracellular survival assays, G-Lisa, siRNA knockdown, immunohistochemistry, immunofluorescence, electron microscopy and luciferase reporter assays. We discuss the strengths and limitations of the methods as well as the different cell model systems applied. Future work should employ new technologies including modern microscopic, proteomics-based and cell signaling approaches to identify and characterise novel virulence mechanisms, which are crucial to provide fresh insights into the diversity of strategies employed by this important pathogen to cause disease. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Cellular invasion; Molecular pathogenesis; Signalling; Virulence